Probabilistic assessment of damaged ship survivability in case of grounding: development and testing of a direct non-zonal approach. (1st July 2016) - Bulian, Gabriele; Lindroth, Daniel; Ruponen, Pekka; Zaraphonitis, George
Abstract: This paper presents the results of ongoing research efforts aimed at the theoretical development and practical implementation of a probabilistic framework for regulatory assessment of ship survivability following grounding accidents, with particular attention to passenger vessels. In the envisioned framework, the probabilities of flooding of a compartment, or a group of compartments, i.e. the so-called "p-factors", are determined using a flexible and easily updatable direct non-zonal approach. The assessment of the conditional ship survivability, on the other hand, is based on the SOLAS "s-factor". The general framework is described, together with implementation details in the specific case of bottom grounding. Testing results, carried out using a specifically developed software tool, are also reported. Highlights: A probabilistic approach for damaged ship survivability assessment is presented. Bottom grounding is addressed, with specific attention to passenger ships. The geometrical and probabilistic model for the considered damage type is described. Damage cases and p-factors are determined by means of a direct non-zonal approach. Testing example results, obtained for a simplified box-shaped ship, are reported.